Hydraulic conveyance of solid capsules - Lazarus, John Henry (Department of Mechanical Engineering, 2016)
The hydraulics of two phase flow of capsule - liquid mixtures is investigated experimentally and analytically. The technology of hydraulic transportation of solid capsules in pipes is advanced to the point of practical feasibility by the development and successful operation of experimental equipment in the laboratory. This involves the innovation of aspects of the technology concerned, such as novel booster pumps, injectors and metering equipment. The effect of independent variables such as capsule geometry, density, roughness and concentration as well as mean water velocity and pipe inclination are investigated. It is shown to what extent these variables affect the dependent variables. A theoretical analysis is presented for the determination of dependent variables, such as capsule velocity, excess energy and power dissipation. Flow conditions around static capsules are shown to be amenable to analysis, supplemented by experimentally determined coefficients. Energy dissipation at the inlet and outlet of static concentric and eccentric capsules is investigated for the first time, and empirical formulations are presented, which are simple and consistent with all the data. A correlation involving a pseudo hydraulic mean radius for analysing the friction head loss in eccentric annuli is presented. There have been numerous investigations concerned with friction head losses in concentric annuli. However, the correlation presented in this thesis is simpler than those given by other investigators and incorporates a wide range of experimental data satisfactorily. A theoretical analysis for flow in annuli of varying eccentricity is also presented in a novel manner and agreement with experiment is evidenced. A study is presented of incipient conditions of capsule motion which indicates a form of empirical equation for excess energy dissipation when capsules are moving.